The technology of the process of storing fruits, vegetables and potatoes and functional-spatial arrangements of objects - Chądzyński, Andrzej; Piróg, Marek (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Proper storage, allowing to keep nutritive values, quality of taste and the aesthetic appearance of products, is possible only in specially for this purpose prepared and equipped objects. A microclimate generated and kept in storage spaces is particularly important (appropriate temperature, relative humidity and air circulation), also an appropriate gases composition of the atmosphere. Conducted analysis of technological thrust in the storage process explains how and using what technical means a production carried out in a storage building should be executed. In the process of preparing the project documentation of the storage object, the technology is a much more important issue than other given matters. It is so, because conclusions and requirements which should be fulfilled so that the building is technically and functionally adapted to storing fruits, vegetables or potatoes. A scope of preliminary and final food processing influences definitive design of the technological sequence of the storage. It appears distinctive in storage buildings that architectural form, structural, material and installation solutions are secondary to the technological processes carried out in the object.